Design and defect study of Cs2AgBiBr6 double perovskite solar cell using suitable charge transport layers. (1st January 2023) - Alkhammash, Hend I; Mottakin, M; Hossen, Md Mosaddek; Akhtaruzzaman, Md; Rashid, Mohammad Junaebur
Abstract: This work modelled and analysed perovskite solar cells based on Cs2 AgBiBr6 with various electron transport layers and hole transport layers. The device structure is fluorine-doped tin oxide (FTO)/ZnO/Cs2 AgBiBr6 /NiO/Au. Power conversion efficiency (PCE) is practically saturated after the perovskite thickness of 700 nm. PCE declines from 21.88% to 1.58% when carrier lifetime decreases from 10 3 ns to 10 −1 ns. Deep-level defects at mid-band gap energy of the perovskite layer can trap both carriers, allowing greater carrier recombination. Carrier capture cross-sectional area greatly impacts on cell performance. When subjected to high temperatures ( T ), the carrier mobility would diminish because carrier scattering increases cell resistance. That is why by raising T from 300 K to 400 K, the value of built-in potential ( V bi ) decreases from 1.17 V to 0.98 V. Device shows maximum efficiency when FTO is used as the front electrode, and Au is used as a back electrode. The optimum device, made of FTO/ZnO/Cs2 AgBiBr6 /NiO/Au, provides V oc = 1.29 V, J sc = 20.69 mA cm −2, fill factor = 81.72%, and PCE = 21.88%.